Uptake of breast reconstruction following mastectomy: a Gold Coast experience. Issue 11 (15th April 2022) - Ho, Debbie; Chan, Erick; Izwan, Sara; Ng, Justin; Teng, Roy; Swindon, Daisy; Chang, Jennifer
Abstract: Background: The breast reconstruction (BR) rate for women undergoing mastectomy for breast cancer management is 18% in Australia. The Australian Access to Breast Reconstruction Collaborative Group recommends that all women should have access to BR. This study presents BR uptake and outcomes from a breast surgical unit. Methods: A retrospective observational study identified women who had curative mastectomy for breast cancer between 1 January 2016 and 31 December 2021. Patient factors and surgical complications were compared between BR and no BR (NBR) patients. Results: Out of 929 women who had a curative mastectomy, 34% underwent reconstruction. Of this, 89% were immediate, and 11% were delayed. Reconstruction increased from 27% (2016) to 35% (2021). During this time, 588 women had a discussion for BR documented at their initial consultation, 58 after initial surgery and 283 were not documented. The rate of discussion prior to mastectomy increased from 38% to 74%. Women who had BR were more likely to be younger, premenopausal and less likely to be diabetic. Complications requiring return to theatre were higher in reconstructed women (13% vs. 7%). Overall, infected seroma, cellulitis requiring intravenous antibiotics and haematoma requiring drainage were comparable between both groups. Conclusion: Our unit achieved a reconstruction rate of 34%, which is higher than national and international averages. Open discussion of reconstruction is crucial for women to make an informed decision. Further prospective studies exploring barriers to timely reconstruction will improve uptake of BR surgery and allow prioritization of BR services in Australia. Abstract : The Australian Access to Breast Reconstruction Collaborative Group recommends that all women undergoing mastectomy for breast cancer should have access to breast reconstruction. Our unit achieved a reconstruction rate of 33%, which is higher than national and international averages. Further prospective studies exploring barriers to timely reconstruction, evaluating patient understanding of complex reconstruction discussions and normalising reconstruction as a standard of care are required.